2020
DOI: 10.1007/s10741-020-09957-5
|View full text |Cite
|
Sign up to set email alerts
|

The Elabela-APJ axis: a promising therapeutic target for heart failure

Abstract: Heart failure (HF) is a growing epidemic with high morbidity and mortality at an international scale. The apelin-APJ receptor pathway has been implicated in HF, making it a promising therapeutic target. APJ has been shown to be activated by a novel endogenous peptide ligand known as Elabela (ELA, also called Toddler or Apela), with a critical role in cardiac development and function. Activation of the ELA-APJ receptor axis exerts a wide range of physiological effects, including depressor response, positive ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 81 publications
0
55
0
1
Order By: Relevance
“…3) [1,6,9,10]. Recently, administration of a miR-122 inhibitor was shown to reduce the key transforming growth factor-β (TGF-β)-induced fibrotic signaling pathway, promotes collagen synthesis and stimulates fibrinogenesis, consequently resulting in the accumulation of fibroblasts and extracellular matrix (ECM), in hypertension and cardiovascular diseases [2,3,9,11]. In our previous study, we observed cardiovascular fibrosis, systolic dysfunction, cardiovascular remodeling and dysfunction in rats after transverse aortic constriction (TAC) or angiotensin II (Ang II) stimulation, and these Central roles of miR-122 in HF, hypertension, MI, atherosclerosis and atrial fibrillation.…”
Section: Biogenesis and Biological Effects Of Mir-122mentioning
confidence: 99%
See 3 more Smart Citations
“…3) [1,6,9,10]. Recently, administration of a miR-122 inhibitor was shown to reduce the key transforming growth factor-β (TGF-β)-induced fibrotic signaling pathway, promotes collagen synthesis and stimulates fibrinogenesis, consequently resulting in the accumulation of fibroblasts and extracellular matrix (ECM), in hypertension and cardiovascular diseases [2,3,9,11]. In our previous study, we observed cardiovascular fibrosis, systolic dysfunction, cardiovascular remodeling and dysfunction in rats after transverse aortic constriction (TAC) or angiotensin II (Ang II) stimulation, and these Central roles of miR-122 in HF, hypertension, MI, atherosclerosis and atrial fibrillation.…”
Section: Biogenesis and Biological Effects Of Mir-122mentioning
confidence: 99%
“…There-fore, miR-122 can cause cardiovascular fibrosis and heart dysfunction, ultimately resulting in hypertension, atherosclerosis, MI and HF. MI myocardial infarction, HF heart failure, ROS reactive oxygen species, LVFS left ventricular fractional shortening, LVEF left ventricular ejection fraction effects were associated with increased levels of miR-122-5p, and reduced levels of SIRT6, elabela (ELA), angiotensin-converting enzyme 2 (ACE2) and phosphorylated adenosine 5 '-monophosphate-activated protein kinase (AMPK) ( Table 1) [1,2,6]. In uric acid-treated HK-2 tubular epithelial cells, treatment with miR-122 mimics markedly increased NLRP3 inflammasome activation by increasing the levels of BRCA1/ BRCA2-containing complex 3 (Table 1) [12].…”
Section: Biogenesis and Biological Effects Of Mir-122mentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis revealed Apela possesses a pair of conserved cysteines, and the last 13 residues are nearly invariant in all vertebrate species [8], which suggests a functional conservation of Apela-APJ pathway. When it comes to functionality, although Apela mRNA is expressed in human stem cells, prostate, and kidney [8,17], and Apela can promote angiogenesis and induce vasodilatation in mouse aorta through activating signal transduction pathways [17], and use as a pre-warning biomarker and a novel therapeutic target against progression of heart failure [18]. In addition, Apela can function as a regulatory RNA to regulate p53-mediated DNA damage-induced apoptosis (DIA) of mouse embryonic stem cells (mESCs) [19].…”
Section: Introductionmentioning
confidence: 99%